2011
DOI: 10.5194/acp-11-13305-2011
|View full text |Cite
|
Sign up to set email alerts
|

Formation of semivolatile inorganic aerosols in the Mexico City Metropolitan Area during the MILAGRO campaign

Abstract: Abstract. One of the most challenging tasks for chemical transport models (CTMs) is the prediction of the formation and partitioning of the major semi-volatile inorganic aerosol components (nitrate, chloride, ammonium) between the gas and particulate phases. In this work the PMCAMx-2008 CTM, which includes the recently developed aerosol thermodynamic model ISORROPIA-II, is applied in the Mexico City Metropolitan Area in order to simulate the formation of the major inorganic aerosol components. The main sources… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 86 publications
2
31
1
Order By: Relevance
“…Tsimpidi et al (2007) showed that a 50 % reduction of NH 3 emissions would lead to a 4 and 9 % decrease in PM 2.5 over the eastern USA in July and January, respectively. The reduction of NH 3 emissions was found to be the most effective PM 2.5 control measure for the winter period over the eastern USA compared to similar reductions of SO 2 , NO x and VOC emissions (Pinder et al, 2008;Tsimpidi et al, 2007Tsimpidi et al, , 2008Karydis et al, 2011). Megaritis et al (2013) and Bessagnet et al (2014) found that over Europe the reduction of NH 3 emissions is the most effective control strategy used to mitigate PM 2.5 in both summer and winter, mainly due to a significant decrease of ammonium nitrate.…”
Section: Introductionmentioning
confidence: 89%
“…Tsimpidi et al (2007) showed that a 50 % reduction of NH 3 emissions would lead to a 4 and 9 % decrease in PM 2.5 over the eastern USA in July and January, respectively. The reduction of NH 3 emissions was found to be the most effective PM 2.5 control measure for the winter period over the eastern USA compared to similar reductions of SO 2 , NO x and VOC emissions (Pinder et al, 2008;Tsimpidi et al, 2007Tsimpidi et al, , 2008Karydis et al, 2011). Megaritis et al (2013) and Bessagnet et al (2014) found that over Europe the reduction of NH 3 emissions is the most effective control strategy used to mitigate PM 2.5 in both summer and winter, mainly due to a significant decrease of ammonium nitrate.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies in the past have shown that the simulation of these effects, especially in areas where dust or sea salt comprises a significant portion of total particulate matter, can considerably improve model predictions (Dentener et al, 1996;Gong et al, 1997;Jacobson, 1999;Jacob, 2000;Song and Carmichael, 2001;Moya et al, 2002;Bian and Zender, 2003;Laskin et al, 2005;Hodzic et al, 2006;Kallos et al, 2007;Astitha and Kallos, 2009;Athanasopoulou et al, 2008Athanasopoulou et al, , 2010Fountoukis et al, 2009;Karydis et al, 2010Karydis et al, , 2011aTsyro et al, 2011;Wang et al, 2012;Im, 2013;Trump et al, 2015). According to their findings, including marine and crustal species in models can substantially affect the phase partitioning of nitrate aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Few of these studies have applied a hybrid approach for aerosol thermodynamics, which combines the dynamic calculation of mass transfer to coarse-mode particles with an equilibrium approach for the fine-mode particles, and found that mineral dust and sea salt can considerably affect the size distribution of aerosol nitrate (Athanasopoulou et al, 2008(Athanasopoulou et al, , 2010Karydis et al, 2010Karydis et al, , 2011aTrump et al, 2015). The presence of mineral cations can also affect the aerosol ammonium concentrations due to thermodynamic interactions with the remainder ions in the aqueous phase (Karydis et al, 2010(Karydis et al, , 2011a. Furthermore, heterogeneous chemistry occurring on dust particles can also act as a source for sulfate (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic NO − 3 and SO 2− 4 mainly contribute to the chemical aging of dust over continents, while sea-salt-derived Cl − is more important over oceans (Sullivan et al, 2007;Fountoukis et al, 2009;Dall'Osto et al, 2010;Tobo et al, 2010;Karydis et al, 2011b;Bougiatioti et al, 2016b;Weber et al, 2016). Apart from the gas-phase composition, the chemical processing of dust also depends on its chemical composition and thus on the source region (Sullivan et al, 2009;Karydis et al, 2016).…”
mentioning
confidence: 99%